2015
DOI: 10.1038/srep09143
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Base Binding Strength and Base Stacking Interaction of DNA Duplex Using Atomic Force Microscope

Abstract: As one of the most crucial properties of DNA, the structural stability and the mechanical strength are attracting a great attention. Here, we take advantage of high force resolution and high special resolution of Atom Force Microscope and investigate the mechanical force of DNA duplexes. To evaluate the base pair hydrogen bond strength and base stacking force in DNA strands, we designed two modes (unzipping and stretching) for the measurement rupture forces. Employing k-means clustering algorithm, the ruptured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Interactions outside the DNA double helix generally play a less important role [ 160 ]. The interplay between hydrogen bonding and stacking interactions in DNA has been the subject of several experimental [ 161 , 162 , 163 , 164 , 165 ] and theoretical investigations [ 159 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Based on DNA melting and energetics of the double helix [ 174 ], it has been recently suggested that in accordance with previous experiments [ 165 , 175 ] the stability of DNA double strands depends mainly on G-C base pair rich sequences.…”
Section: Conclusion and Outlookmentioning
confidence: 99%
“…Interactions outside the DNA double helix generally play a less important role [ 160 ]. The interplay between hydrogen bonding and stacking interactions in DNA has been the subject of several experimental [ 161 , 162 , 163 , 164 , 165 ] and theoretical investigations [ 159 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Based on DNA melting and energetics of the double helix [ 174 ], it has been recently suggested that in accordance with previous experiments [ 165 , 175 ] the stability of DNA double strands depends mainly on G-C base pair rich sequences.…”
Section: Conclusion and Outlookmentioning
confidence: 99%
“…The universal anchor sequence length was increased by 5 nt on the 5’ end relative to the sequence reported by Todhunter et al 36 in order to increase duplex length 37 when hybridized to the detection oligonucleotide, which was also purchased from IDT. The detection oligonucleotide was based on the Arabidopsis thaliana FRK1 gene because of its lack of sequence homology with human and viral genes.…”
Section: Methodsmentioning
confidence: 99%
“…In combination with standard wide-field or total internal reflection microscopy the spatiotemporal distribution of forces can be determined at high resolution, which is only limited by the optical resolution (~0.2 µm). The mechanical stability of dsDNA depends on its length and the GC content (Zhang et al, 2015). The force F1/2 that is required to unfold 50% of the DNA sensors, has been calibrated in previous single-molecule studies between ~4-60 pN for varying DNA sequences (Wang and Ha, 2013;Zhang et al, 2014).…”
mentioning
confidence: 99%